Implicit effect of abstract/concrete components in the categorization of Chinese words. Issue 5 (4th July 2022) - D'Aversa, Francesco Mayo; Lugli, Luisa; Borghi, Anna M.; Barca, Laura
ABSTRACT: This study extends the examination of the difference between abstract concepts to the Chinese language and its peculiar characteristics in word formation, where components with different semantic content might be aggregated within a word. Native Chinese speakers categorised abstract and concrete words by moving the computer mouse towards their choice. Stimuli with a "semantically simple structure" (i.e. abstract-abstract/concrete-concrete) were compared with those with a "mixed structure" (i.e. abstract-concrete/concrete-abstract) to test for an effect of the conceptual content of the stimulus's components on its overall processing. Response time and kinematic parameters revealed that: a) the semantic content of the components affected the processing of abstract but not concrete concepts, b) concepts differed when they have a semantically mixed structure, not a simple one. We extend the concreteness effect to logographic script and provide evidence that the presence of a concrete component within an abstract concept is elaborated and affects its processing.